Nanometals incorporation into active and biodegradable chitosan films - Dordevic, Simona; Dordevic, Dani; Tesikova, Karolina; Sedlacek, Petr; Kalina, Michal; Vapenka, Lukas; Nejezchlebova, Marcela; Treml, Jakub; Tremlova, Bohuslava; Koudelková Mikulášková, Hana (Heliyon, 2024)
This study investigates the effects of incorporating ZnO, TiO2, and colloidal Ag nanoparticles on the antioxidant, antimicrobial, and physical properties of biodegradable chitosan films. The research focuses on addressing the growing demand for sustainable packaging solutions that offer efficient food preservation while mitigating environmental concerns. In this investigation, the physical properties including thickness, water content, solubility, swelling degree, tensile strength, and elasticity of the chitosan films were examined. Additionally, the samples were analyzed for total polyphenol content, antimicrobial activity, and antioxidant capacity. Notably, the incorporation of ZnO nanoparticles led to the lowest water content and highest strength values among the tested films. Conversely, the addition of colloidal Ag nanoparticles resulted in films with the highest antioxidant capacities (DPPH: 32.202 ± 1.631 %). Remarkably, antimicrobial tests revealed enhanced activity with the inclusion of colloidal silver nanoparticles, yet the most potent antimicrobial properties were observed in films containing ZnO (E.coli: 2.0 ± 0.0 mm; MRSA: 2.0 ± 0.5 mm). The findings of this study hold significant implications for the advancement of edible biodegradable films, offering potential for more efficient food packaging solutions that address environmental sustainability concerns. By elucidating the effects of nanoparticle incorporation on film properties, this research contributes to the ongoing discourse surrounding sustainable packaging solutions in the food industry.
Keywords: Nanoparticles; Chemical and physical characterization; Packaging